Anti-allergic effects of Marmin, a coumarine isolated from Aegle marmelos Correa: In vitro study - Agung Endro Nugroho,; Sugeng Riyanto,; Mohamad Aspollah Sukari,; Kazutaka Maeyama, (International Journal of Phytomedicine, 2011)
Marmin or (7-(6’,7’-dihydroxygeranyl-oxy)coumarin is an active compound isolated from Aegle marmelos Correa. The study aimed to investigate the effects of marmin on the histamine release from rat mast cell. The study was performed by using rat basophilic leukemia (RBL- 2H3) cell line and rat peritoneal mast cells (RPMCs). The histamine release from these cells was determined by using HPLC fluorometric method. In this study, marmin succeeded to inhibit the histamine release from RBL-2H3 cell line induced by DNP24-BSA, thapsigargin or ionomycin. In addition, marmin suppressed 45Ca2+ influx on RBL-2H3 cell line induced by thapsigargin. Marmin also succeeded to inhibit the histamine release from RPMCs induced by thapsigargin. However, marmin showed weak inhibitory effects on the histamine release from RPMCs induced by compound 48/80, PMA or ionomycin. Based on the results, the inhibitory effect of marmin on the histamine release from mast cells high depends on the type of mast cell and also involves mechanisms related to intracellular Ca2+ signaling events by blocking Ca2+ influx into mast cells.